Foot biomechanics and injury risk factors in youth football players: A cross-sectional study - Sinen, Hamza; Ghanbarian, Amirhossein (Sport, Exercise, and Injury, 2026)
Background: Altered plantar pressure distribution and foot alignment have been suggested in previous studies to be associated with ankle instability and overuse injuries; however, evidence in youth populations remains limited. Objectives: This study aimed to investigate foot biomechanics and potential injury risk factors in youth football players aged 5–15 years. Methods: This study employed an analytical cross-sectional design involving 30 youth football players recruited from local football academies. Participants were categorized into three age groups: 5–9 years (n = 10), 10–12 years (n = 10), and 13–15 years (n = 10). Data were collected through pedobarographic plantar pressure assessment, hallux valgus angle (HVA) measurement using a goniometer, navicular drop test (NDT), and subtalar angle assessment. Statistical analyses included descriptive statistics, Shapiro–Wilk normality test, Pearson correlation, independent t-test, and one-way ANOVA with effect size (η²). A significance level of p ≤ 0.05 was applied. Results: The results showed that hindfoot plantar pressure was higher than forefoot pressure in both feet, indicating a posterior loading pattern. Hallux valgus angles were within normal ranges, while subtalar angles demonstrated a tendency toward pronation. Significant differences were observed in left foot HVA and left hindfoot pressure across age groups (p < 0.05), with moderate effect sizes (η² = 0.20–0.21). Correlation analysis revealed moderate to strong positive relationships between subtalar pronation and HVA variables. Conclusions: Youth football players exhibit biomechanical characteristics, such as increased hindfoot loading and subtalar pronation, that may represent adaptive responses to sport-specific demands and be associated with potential injury risk. However, given the study’s cross-sectional design, these findings should be interpreted as descriptive biomechanical patterns rather than as direct predictors of injury. Early biomechanical screening and targeted preventive training may help support optimal athletic development.